Beaver‐created successional gradients increase β‐diversity of invertebrates by turnover in stream‐wetland complexes. (8th April 2019) - Bush, Bryana M.; Stenert, Cristina; Maltchik, Leonardo; Batzer, Darold P.
Abstract: Beavers are ecosystem engineers known to modify the environment primarily via dam building. Beaver wetlands are complexes of newly created, mature, and abandoned beaver constructions within a stream network. Invertebrate dynamics across all habitats derived from these successional stages remains poorly explored. Here, we test how this natural successional gradient created by beaver affects invertebrate β‐diversity and its components (turnover and nestedness). Invertebrates were sampled in the Piedmont region of Georgia (U.S.A.) in two seasons (autumn and spring) in each of four stages of habitat succession: natural stream channels, forested wetlands created by newly formed beaver dams, mature open wetland marshes, and abandoned wetland meadows. In autumn, invertebrate communities were different among successional stages, apart from new versus abandoned wetlands and new versus mature wetlands, which were only marginally different, and streams versus abandoned wetlands. In spring, only the mature beaver wetland communities were unique, differing from both streams and from newly formed or abandoned wetlands. Beta‐diversity was nearly twice as high for the overall study‐system than any individual successional stage, which all had similar diversity. Additionally, turnover was significantly higher than nestedness in all stages. Community differences combined with high turnover among successional stages indicates that beaver wetland communities are not merely a subset of more stable mature wetlands or streams; instead, each stage has a different taxonomic make‐up. Our results strengthen the idea that beaver activity can be an important conservation tool by contributing substantially to diversity in areas where they are present. Beaver wetlands have the potential to help stabilise β‐ and regional diversity in the face of wetland loss from climate change and other human impacts.